Workforce Skills in the Eyes of the Employers : Results of the Georgia STEP Employer Skills Survey - Rutkowski, Jan (World Bank, Washington, DC, 2015)
The objective of this note is to present the results of the recently completed employer skills survey, and to discuss their policy implications. The analysis finds that there is a skills shortage in Georgia despite high unemployment. It is difficult for employers, especially in the modern sector, to find workers with the required skills. Employers demand not only ‘hard’ technical skills, but also ‘soft’ social and behavioural skills (such as openness to experience) as well as higher-order cognitive skills (such as problem solving and creative thinking). And these are the skills that young Georgians often lack. Box one summarizes the main results of the analysis and shows the core employability skills that young workers lack most often. The note is organized as follows. Section one looks at the supply of and demand for skills, and shows that, despite high unemployment, there is a skills shortage. Section two examines the demand for skills more closely. It identifies skills that determine the employers hiring decisions, and skills that young job applicant most frequently lack. Section three focuses on firm organized training as a way of coping with a skills shortage. Section four concludes and discusses policy implications of the analysis.